2020
DOI: 10.3389/fmicb.2020.02061
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Staphylococcus epidermidis O47

Abstract: The skin colonizing coagulase-negative Staphylococcus epidermidis causes nosocomial infections and is an important opportunistic and highly adaptable pathogen. To gain more insight into this species, we sequenced the genome of the biofilm positive, methicillin susceptible S. epidermidis O47 strain (hereafter O47). This strain belongs to the most frequently isolated sequence type 2. In comparison to the RP62A strain, O47 can be transformed, which makes it a preferred strain for molecular studies. S. epidermidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 114 publications
5
19
0
Order By: Relevance
“…IS256 has been shown to facilitate genomic rearrangements in pathogenic S. epidermidis isolates ( Cabrera-Contreras et al, 2019 ). The detection of IS families IS110, IS200/IS605, and IS3 agrees with a study of Raue et al (2020) , which also found the IS family IS6 was not detected in the current study. Again, the detection of IS256 and the ica operon in isolates belonging to ST2 agrees with a study conducted in China, which analyzed S. epidermidis from community and hospital environments ( Du et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…IS256 has been shown to facilitate genomic rearrangements in pathogenic S. epidermidis isolates ( Cabrera-Contreras et al, 2019 ). The detection of IS families IS110, IS200/IS605, and IS3 agrees with a study of Raue et al (2020) , which also found the IS family IS6 was not detected in the current study. Again, the detection of IS256 and the ica operon in isolates belonging to ST2 agrees with a study conducted in China, which analyzed S. epidermidis from community and hospital environments ( Du et al, 2013 ).…”
Section: Discussionsupporting
confidence: 92%
“…The detection of blaZ in all isolates and the regulator genes blaR and blaI may explain the resistance against penicillin and cephalosporins observed in antibiotic susceptibility tests, which is in agreement with a previous study (Cabrera-Contreras et al, 2019). S. epidermidis isolates carrying similar resistance gene profiles have been previously reported (Xu et al, 2018;Cabrera-Contreras et al, 2019;Raue et al, 2020). Generally, there was considerable agreement between resistance phenotypes and genotypes observed with ARGs affirming the phenotype, except in a few instances.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…SnapGene Viewer v.6.0.2 was used for the visualization of gene cassettes. Virulence genes were investigated using the virulence factor database (VFDB) [ 53 ], using S. epidermidis RP62A as a reference strain for comparison [ 54 ].…”
Section: Methodsmentioning
confidence: 99%